Agent‐based identification and control of voltage emergency situations. Issue 6 (13th February 2018) - Robitzky, Lena; Weckesser, Tilman; Häger, Ulf; Rehtanz, Christian; Van Cutsem, Thierry
Abstract : Changing dynamics of power systems caused by the migration from conventional to distributed energy sources increase the risk of blackouts due to voltage instability, especially in case of unforeseen network conditions (e.g. (N‐k)‐cases). To enable both secure and efficient power supply, novel monitoring and emergency control systems for the identification of voltage emergency situations as well as the execution of control actions are required that react reliably in due time and adaptively in the case of changing network situations. This study presents a distributed agent‐based approach to counteract voltage instability that is based solely on local measurements and limited inter‐agent communication. Distributed agents located at substations in the (sub‐)transmission network monitor distribution and transmission voltages, as well as, load tap changer positions and are able to autonomously curtail load in case system stability is endangered. The applicability of the approach is demonstrated in a co‐simulation environment interfacing the multi‐agent system with a dynamic power system simulation. The presented approach allows for an early detection of voltage instability as well as a coordinated execution of available control actions.